Assessment of efficiency of military transport units using the DEA and SFA methods - Despić, Dejan R.; Bojović, Nebojša J.; Kilibarda, Milorad J.; Kapetanović, Marko V. (Vojnotehnički glasnik / Military Technical Courier, 2018)
The aim of the paper is to make an analysis of the efficiency of selected transport units in the military logistics and military vehicles in carrying out the tasks of cargo transport using the method of stochastic frontier analysis (SFA) and the data envelopment analysis (DEA), and creating the basis for further investigation of the parameters that influence the efficiency of military transport units and military vehicles. The research was carried out in ten military transport units intended for the realization of tasks dealing with the logistic function of movement and transportation. The efficiency analysis was done for military vehicles used for carrying out cargo transportation tasks for the needs of supply and special needs of command, units and military institutions. The data was obtained from the software package used to monitor the exploitation of military motor vehicles in the period of one calendar year. The results show that the method selection has a major impact on the obtained technical efficiency assessments, and therefore on possible management decisions based on the performed efficiency analysis.
Keywords: stochastic frontier analysis.; data envelopment analysis; military vehicles; military transport units; efficiency